RECENT SCHOLARSHIP ON “ISLAMISM” DISCOURSE: AN EVALUATION AND ASSESMENT - Tauseef Ahmad Parray (Balai Penelitian dan Pengembangan Agama Semarang, 2016)
The events of 9/11 era had a number of dramatic results for ‘Islam’ and the Muslim world; and one such result was a surplus of endeavors through various mediums to conceptualize, hypothesize, and posit an ostensible ‘divide’ between ‘Islam’ (as a religion, ideology, and political system) and Western culture and society. In post- 9/11 era, Islam was frequently used as a ‘violent’ and ‘terrorist’ religion and, on the other, there has been a prodigious demand for information about Islam, and things related to Islam. It gave a momentum, in the years to come, to an issue (among a multiple of issues and discourses) referred as “Islamism”—a term/ label, in many senses, used collectively but commonly for “Islamic fundamentalism”, “Islamic extremism”, “Islamic conservatism”, “radicalism”, “political Islam”, etc. This paper, in this backdrop, presents an assessment of the recent scholarship on “Islamism” as a discourse. It highlights and presents a detailed evaluation and estimation, with some critical and comparative notes, on some important works dealing with various aspects and facets of Islamism (radicalism and political Islam), and puts forward some insights on the future prospects of ‘Islamism’ as a discourse.